Prevalence and determinants of contraceptive method use among Bangladeshi women of reproductive age: a multilevel multinomial analysis - Satyajit Kundu; Subarna Kundu; Md. Ashfikur Rahman; Humayun Kabir; Md. Hasan Al Banna; Saurav Basu; Hasan Mahmud Reza; Ahmed Hossain (BMC, 2022)
Abstract Background Much scholarly debate has centered on Bangladesh's family planning program (FPP) in lowering the country's fertility rate. This study aimed to investigate the prevalence of using modern and traditional contraceptive methods and to determine the factors that explain the contraceptive methods use. Methods The study used data from the 2017-18 Bangladesh Demographic and Health Survey (BDHS), which included 11,452 (weighted) women aged 15-49 years in the analysis. Multilevel multinomial logistic regression was used to identify the factors associated with the contraceptive method use. Results The prevalence of using modern contraceptive methods was 72.16%, while 14.58% of women used traditional methods in Bangladesh. In comparison to women in the 15-24 years age group, older women (35-49 years) were more unwilling to use modern contraceptive methods (RRR: 0.28, 95% CI: 0.21-0.37). Women who had at least a living child were more likely to use both traditional and modern contraceptive methods (RRR: 4.37, 95% CI: 3.12-6.11). Similarly, given birth in the previous 5 years influenced women 2.41 times more to use modern method compared to those who had not given birth (RRR: 2.41, 95% CI: 1.65-3.52). Husbands'/partners' decision for using/not using contraception were positively associated with the use of both traditional (RRR: 4.49, 95% CI: 3.04-6.63) and modern methods (RRR: 3.01, 95% CI: 2.15-4.17) rather than using no method. This study suggests rural participants were 21% less likely to utilize modern methods than urban participants (RRR: 0.79, 95% CI: 0.67-0.94). Conclusion Bangladesh remains a focus for contraceptive use, as it is one of the most populous countries in South Asia. To lower the fertility rate, policymakers may design interventions to improve awareness especially targeting uneducated, and rural reproductive women in Bangladesh. The study also highlights the importance of male partners' decision-making regarding women's contraceptive use.